Progress, trends and development of drying studies on coconut kernel products: a review - Sahari, Yahya; Anuar, Mohd Shamsul; Mohd Nor, Mohd Zuhair; Abdul Ghani, Nur Hamizah; Mohd Tahir, Suraya (UPM Press, 2023)
There are several different forms of coconut kernel products, such as copra, desiccated coconut, coconut chips, strips, and flakes, each with its identity, industrial standard, and use in the food sector. In view of this, many studies concentrate on drying kinetics and the quality of the final dried product and extend from laboratory-scale research to industrial operations. This article discusses the application of various drying processes for various types of coconut kernel products, the pre-treatment involved prior to drying and some qualitative aspects associated with the final product. The use of mathematical modelling in various drying techniques was also examined and compared in this article. The effects of drying parameters such as air temperature, velocity, and pre-treatment on drying rate, time, colour quality, energy consumption, and yield are particularly interesting. Future suggestions and directions are emphasised and featured to fill the research gap in this product and sector.